Nuevos registros de Galeocerdo cuvier (Carcharhinidae) como pesca incidental de la pesca artesanal peruana - Roque-Sanchez, Maximo (2025)
Two new records of the tiger shark Galeocerdo cuvier (Péron & Lesueur, 1822) are reported from artisanal fisheries along the central coast of Peru. The specimens were incidentally captured during fishing operations targeting Myliobatis peruvianus and Pseudobatos planiceps. The first individual was caught in the Bajada de Cañete fishing area (Lima Department) and landed at the Lagunilla Artisanal Fishing Landing Site (DPA) on 11 July 2023; it measured 91 cm in total length (TL). The second specimen was caught off Yumaque Beach (Pisco, Ica) and landed at the San Andrés DPA on 1 September 2023, with a TL of 95 cm. Both individuals were captured using 10-inch gillnets. These occurrences took place during the anomalous warming event associated with the 2023 Coastal El Niño.